Design and analysis of advanced SAW/BAW based wireless transceiver and sensor circuits and systems - Zhu, Yao (2015)
The new fields of wireless transceivers and sensor networks utilizing surface acoustic wave (SAW) and bulk acoustic wave (BAW) devices have drawn significant attention, since the high quality factor (Q>1000) and high frequency (up to Gigahertz) characteristics of these devices greatly enhance the noise and power performance, and reduce the complexity of the systems. The major contribution of this thesis is to propose an optimized system design methodology by co-designing the SAW/BAW resonators and CMOS circuits. Accurately modeling and analyzing the effects of the resonators makes it feasible to optimize the power consumption and noise performance in system level. In more details, we designed: a) Ultra low-power and low-phase-noise oscillators; b) Energy efficient frequency shift keying (FSK) modulators; c) A power scavenging wireless temperature sensor. Both the simulation and measurement results are provided for the above designs which have validated the proposed optimization design methodology.